EDUKASI ANTI BULLYING MELALUI KEGIATAN LITERASI SOSIAL BAGI SISWA SMK NEGERI 2 KOLAKA - Miswara Gandi; Sri Rahlia; Risna; Novita Sari Hamka; Nasyah Fauziyah Misran; Agustina; Sarmadan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Bullying is one of the social problems that frequently occurs in schools and can have negative impacts on students’ psychological, social, and academic development. Therefore, effective prevention efforts are needed through educational approaches that instill the values of empathy, tolerance, and mutual respect. This article aims to examine the role of social literacy activities as a medium for anti-bullying education for students. The method used in writing this article is a literature study by analyzing various relevant sources related to bullying, social literacy, and character education in schools. The results of the study indicate that social literacy activities, such as reading stories themed around empathy, group discussions, reflection on social values, and writing about social experiences, can increase students’ awareness of the impacts of bullying and encourage the development of respectful behavior toward others. Through social literacy activities, students not only gain knowledge but also develop critical thinking skills, empathy, and social skills. Therefore, the integration of anti-bullying education through social literacy activities can be an effective strategy in creating a safe, inclusive school environment that supports the character development of students.